Unitary inhibitory synaptic potentials in the guinea-pig hippocampus in vitro. - Miles, R (1984)
Mechanisms involved in the generation of synaptic inhibition have been investigated by making simultaneous intracellular recordings from pairs of neurones in the CA3 pyramidal cell field of guinea-pig hippocampal slices. Inhibitory post-synaptic potentials dependent on single presynaptic action potentials (i.p.s.p.s) and mediated through monosynaptic and disynaptic connexions have been identified. The recurrent nature of some hippocampal inhibition has been demonstrated by showing that activity in a single cell may initiate feed-back i.p.s.p.s onto itself. The observation of synchronous i.p.s.p.s in recordings from two cells illustrates the divergence of synaptic contacts made by inhibitory neurones. The peak conductance change associated with an i.p.s.p. was in the range 5-9 nS and it reversed uniformly throughout its time course at membrane potentials between -73 and -80 mV. The shortest time-to-peak of synaptic potentials was approximately 3 ms and in this case the i.p.s.p. decayed with a time constant comparable to the passive membrane time constant of the post-synaptic neurone. The peak amplitude of i.p.s.p.s fluctuated in a way consistent with the quantal release of inhibitory neurotransmitter. Inhibitory neurones could fire bursts of action potentials not unlike those generated by pyramidal cells in this area. A comparison of the conductance change associated with identified i.p.s.p.s with that associated with the maximal inhibitory post-synaptic potential resulting from electrical stimulation of fibre pathways suggested that, in the slice, a pyramidal cell is innervated by up to fifteen inhibitory neurones.